PRINCIPAL MANAGEMENT IN OPTIMIZING TEACHER PERFORMANCE IN SOCIAL STUDIES LEARNING AT SDN 8 TERNATE CITY - Dede Ferdian Rosita; Mohtar Kamisi; Irwan Djumat (SOSIOEDUKASI, 2025)
This study aims to analyze the role of school principal management in optimizing teacher performance in Social Sciences (IPS) learning at SDN 8 Ternate City. The research approach used is qualitative descriptive with data collection techniques through interviews, observations, and documentation. The results of the study show that school principals have a strategic role in four management functions, namely: (1) planning, by developing a program to improve teacher competency through training and development of learning tools; (2) organization, by forming cooperation between teachers through working groups and clear division of tasks; (3) implementation, by creating a conducive work climate, motivating, and encouraging the use of innovative methods in social studies learning; and (4) supervision, by carrying out regular learning supervision to provide constructive feedback. Effective principal management has been proven to be able to improve teacher professionalism, improve the quality of social studies learning, and support the improvement of student learning outcomes.